JAKARTA ISLAMIC INDEX STOCK MARKET REACTION TO TURMOIL ISRAEL AND PALESTINE WAR - Syifa Azzahra; Ristati; Marzuki; Ghazali Syamni (PT. Radja Intercontinental Publishing, 2024)
This research aims to analyze the reaction of the Jakarta Islamic Index stock market to the turmoil of the Israeli andPalestinian war. The data used in this research is secondary data from 14 samples. The sampling technique used was purposive sampling technique. The method used to analyze differences before and after the turmoil of war is the paired t test. The research results show that statistically using abnormal returns it can be concluded that there is no difference in the reaction of the Jakarta Islamic Index stock market before and after the turmoil of the Israeli and Palestinian wars with a significance value of 0.184 < 0.05. Meanwhile, by using trading volume activity, it can be concluded that there is a difference in the reaction of the Jakarta Islamic Index stock market before and after the turmoil of the Israeli and Palestinian wars with a significance value of 0.001 < 0.05. This indicates that there was a change in stock prices after the turmoil of the Israeli and Palestinian war.